2014
DOI: 10.1002/2014gl060755
|View full text |Cite
|
Sign up to set email alerts
|

Study of a global auroral Pc5 pulsation event with concurrent ULF waves

Abstract: We present results from a study of concurrent, periodic variations in auroral luminosity (auroral pulsations) and in magnetospheric plasma/magnetic field data. This event occurred on 10 March 2010 from~13 to 17 UT during an extended southward interplanetary magnetic field and was probably triggered by a slow shock. The auroral pulsations, as measured by the Ultraviolet Imager on board the Polar satellite, were long lasting (~2.5 h), monochromatic (~2.5 mHz), large scale, and appeared in the night sector aurora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Although we have primarily discussed the possible role of compressional Pc5 pulsations on the daytime auroral pulsations, we cannot completely rule out a potential interaction process of energetic electrons with poloidal Pc5 pulsations because THEMIS-D observed the large E φ oscillations. However, we refrain further discussion here, because Liou and Sibeck (2014) and Motoba et al (2015) have already argued the possible contribution of poloidal Pc5 pulsations to the nightside diffuse auroral pulsations.…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have primarily discussed the possible role of compressional Pc5 pulsations on the daytime auroral pulsations, we cannot completely rule out a potential interaction process of energetic electrons with poloidal Pc5 pulsations because THEMIS-D observed the large E φ oscillations. However, we refrain further discussion here, because Liou and Sibeck (2014) and Motoba et al (2015) have already argued the possible contribution of poloidal Pc5 pulsations to the nightside diffuse auroral pulsations.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…In contrast to many examples of periodic auroral arcs which display FLR-related pulsation characteristics, only a few studies reported long-period pulsations in the diffuse aurora (Liou & Sibeck, 2014;Taylor et al, 1989;Yamamoto et al, 1988). Using ground-based all-sky TV and magnetometer data, Yamamoto et al (1988) demonstrated examples of which the diffuse auroral luminosity in the dawn sector was modulated in concert with Pc5 geomagnetic pulsations on the ground.…”
mentioning
confidence: 99%
“…Saka et al () reported evidence for a close association between auroral pulsations and a strong poloidal component of the Pc 5 magnetic field oscillations observed on the ground. More recently, Liou and Sibeck () found that some long‐duration, monochromatic Pc5 auroral pulsations are associated with ULF waves at the same frequency observed concurrently in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This type of auroral pulsation is often accompanied by magnetic pulsations. Auroral pulsations have been observed not only from the ground (Yamamoto et al, 1988) but also in space (Liou et al, 2008;Liou & Sibeck, 2014;Liou & Takahashi, 2013). The long-period auroral pulsations are usually tied to discrete auroras (e.g., arcs) (Samson et al, 1996;Xu et al, 1993) and are thought to be associated with field line resonances (Samson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, electrostatic electron cyclotron harmonic and electromagnetic chorus waves have been identified as drivers. Recently, auroral intensity modulations with a much longer period (~400 s) and extended over an extensive region were reported by Liou and Sibeck [].…”
Section: Introductionmentioning
confidence: 99%